2016
DOI: 10.1002/celc.201600030
|View full text |Cite
|
Sign up to set email alerts
|

Structural Study of Electrochemically Lithiated Si(111) by using Soft X‐ray Emission Spectroscopy Combined with Scanning Electron Microscopy and through X‐ray Diffraction Measurements

Abstract: The structure, composition, and electronic state of electrochemically lithiated Si(111) were investigated by using soft X‐ray emission spectroscopy (SXES) combined with scanning electron microscopy (SEM) and by using X‐ray diffraction (XRD) with synchrotron radiation (SR). When the SXES results were compared with the calculated density of state (DOS), we found that three kinds of electrochemically lithiated Si (EC‐LiSi) phases were formed on the Si(111) substrate, that is, a single‐crystalline Li15Si4 (sc‐Li15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(57 citation statements)
references
References 45 publications
(93 reference statements)
4
51
2
Order By: Relevance
“…Moreover, the energy position of the emission peak of a-Li 13 Si 4 is 0.55 eV higher in energy if compared with the one of a-Li 15 Si 4 . Therefore it is unlikely that a-Li 13 Si 4 gives noticable contribution to the XES of the second layer observed by Aoki et al 76 The analysis of the Si-L The analysis performed above clearly demonstrates that combination of the theoretical and experimental methods of the soft X-ray emission spectroscopy can be used as a powerful tool for the comprehensive analysis of the anode materials in LIBs.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…Moreover, the energy position of the emission peak of a-Li 13 Si 4 is 0.55 eV higher in energy if compared with the one of a-Li 15 Si 4 . Therefore it is unlikely that a-Li 13 Si 4 gives noticable contribution to the XES of the second layer observed by Aoki et al 76 The analysis of the Si-L The analysis performed above clearly demonstrates that combination of the theoretical and experimental methods of the soft X-ray emission spectroscopy can be used as a powerful tool for the comprehensive analysis of the anode materials in LIBs.…”
Section: Resultsmentioning
confidence: 83%
“…Recently, the structure, composition and electronic state of electrochemically lithiated Si(111) have been studied by methods of soft X-ray spectroscopy (SXES) combined with the X-ray diffraction with synchrotron radiation. 76 It has been reported that three different In the present work we perform theoretical analysis of the mechanisms of formation of the soft X-ray Si-L 2,3 emission of crystalline and amorphous Li x Si alloys. On the base of comparison of results of our calculations with the available experimental data we demonstrate that methods of SXES can be used as a powerful tool for the comprehensive analysis of the electronic and structural properties of crystalline and amorphous Li x Si alloys in LIBs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 In region (B), i.e., (iv), a-Li 2.5 Si is lithiated further to c-Li 15 Si 4 and a-Li x Si (2.5<x<3.75). [16][17][18][19][20] An outermost c-Li 15 Si 4 layer is formed as observed by in-situ TEM, 17,18 soft X-ray photoelectron spectroscopy (SXES) 20 and XRD 19,20 and its formation results from the highest Li concentration and energetic stability. 18 In region (C), i.e., (v) and (vi), a-Li x Si (2.5<x<3.75) is delithiated to a-Li 2 Si, 16 and then in region (D), i.e., (vii) and (viii), c-Li 15 Si 4 is delithiated to a-Li 2 Si, [16][17][18][19] because of higher stability of c-Li 15 Si 4 than a-Li 15 Si 4 .…”
Section: Resultsmentioning
confidence: 97%